2010
DOI: 10.1111/j.1365-294x.2010.04736.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological specialization in mycorrhizal symbiosis leads to rarity in an endangered orchid

Abstract: Terrestrial orchid germination, growth and development are closely linked to the establishment and maintenance of a relationship with a mycorrhizal fungus. Mycorrhizal dependency and specificity varies considerably between orchid taxa but the degree to which this underpins rarity in orchids is unknown. In the context of examining orchid rarity, large scale in vitro and in situ germination trials complemented by DNA sequencing were used to investigate ecological specialization in the mycorrhizal interaction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
132
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(141 citation statements)
references
References 51 publications
7
132
1
1
Order By: Relevance
“…By comparison, parasitisms having relatively high species-specificity have been shown to involve switching between more distantly related plants [42]. Generally, host-range limits vary between antagonistic associations compared to symbioses and mutualisms where narrower species-to-species dependencies are more common [43-45]. Parasites of the galling habit exhibit wider host ranges than that of the prey species and evolve host-plant conservatism as a secondary association [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, parasitisms having relatively high species-specificity have been shown to involve switching between more distantly related plants [42]. Generally, host-range limits vary between antagonistic associations compared to symbioses and mutualisms where narrower species-to-species dependencies are more common [43-45]. Parasites of the galling habit exhibit wider host ranges than that of the prey species and evolve host-plant conservatism as a secondary association [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Mycorrhizal fungi can affect the diversity of plant communities (Van der Heijden et al. 1998) and potentially the distribution of plant species (Swarts et al. 2010).…”
Section: Introductionmentioning
confidence: 99%
“…While the rarity of species has been linked to a wide range of ecological traits (Schemske et al. 1994; Bevill & Louda 1999), only one previous study has tested the role of mycorrhizal fungi in causing rarity of the host (Swarts et al. 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Orchid species that associate with a limited number of fungi or fungi with a narrow distribution area can be hypothesized to be more vulnerable to changes in mycorrhizal abundances than orchid species that associate with a large suite of mycorrhizal fungi or fungi with a very broad distribution [10]–[12]. Although convincing evidence is still lacking, recent analyses of mycorrhizal associations in the Australian genus Caladenia have shown that mycorrhizal associations combined with other environmental factors can have a strong influence on plant rarity [12]. On the other hand, no relationship was found between orchid rarity and mycorrhizal specificity in the genus Drakaea .…”
Section: Introductionmentioning
confidence: 99%